Deserving poor and the desirability of a minimum wage - Tomer Blumkin; Leif Danziger (IZA Journal of Labor Economics, 2018)
This paper provides a normative justification for the use of a minimum wage as a redistributive tool in a competitive labor market. We show that a government interested in improving the wellbeing of the deserving poor, while being less concerned with their undeserving counterparts, can use a minimum wage to enhance the efficiency of the tax-and-transfer system in attaining this goal.
Keywords: D6; H2; H5; 330; Deserving poor; Minimum wage; Welfare; Redistribution